Development of Flipbook Art Media in Improving Early Childhood Reading Skills at RA - Tika Anfalyani; Noor Baiti; Herman Taufik; Uswatun Nisa (EDUJAVARE: International Journal of Educational Research, 2025)
Early childhood education (ECE) forms a vital foundation for children’s cognitive, linguistic, emotional, and social development. This study aims to develop and evaluate Flipbook Art as a digital learning media to enhance early reading skills among children aged 5–6 years at RA Al-Mushallun, Kecamatan Alalak. Employing a Research and Development (R&D) approach with the Four-D (Define, Design, Develop, Disseminate) model, the research produced an interactive flipbook tailored for early learners. Validation was conducted by material and media experts as well as classroom teachers, followed by small and large-scale trials involving 100 children. Results indicate that Flipbook Art is highly feasible (validated at >80% by all validators) and effective in improving children’s ability to recognize letters, decode sounds, comprehend words, and develop reading fluency. The integration of visual design, interactive features, and curriculum alignment proved vital in fostering literacy engagement. The study recommends Flipbook Art as an innovative, accessible solution for addressing early reading challenges and supporting teachers in early childhood education settings.